Simultaneous SO₂/NOₓ removal from flue gas using catalyzed adsorbents - Silas, Kiman (2019)
The fossil fuels consumption is the primary source of anthropogenic air pollution. Carbon dioxide (CO2) is the most prominent agent that contributes to global climate change. However, the threats of the other flue gas compositions such as the acid gases are constantly overlooked. The presence of sulphur dioxide and nitrogen dioxide (SO2 and NOx) will reduce the efficiency of CO2 capture while their reaction with moisture will form acidic solutions which greatly reduce the life span of pipelines and instrumentations. Furthermore, it also causes environmental and properties degradation with health effects such as lung irritation, stroke, respiratory problems, asthma, nose and throat irritation. Meanwhile, the multi-step SO2/NOx removal techniques are complex with high capital cost, solvent losses, unwanted foaming, flooding, equipment fouling and corrosive and others. Thus, the simultaneous removal of SO2/NOx from flue gas by adsorption is a promising alternative. This work investigates the deposition precipitation, wet pore volume impregnation and hydrothermal methods of synthesizing activated carbon monolith (ACM) supported metal oxide adsorbents (Co3O4, CuO, V2O5 and CeO2). A total of twelve adsorbents were developed and the activity tests were performed for real flue gas generated from coal burning to capture SO2 and NOx. Based on the breakthrough studies, the hydrothermally synthesized ACM with Co3O4 showed the best performance according to the breakthrough studies. The HM-Co3O4/ACM catalyzed adsorbent demonstrates high adsorption capacity for SO2 and NOx of 123.1 and 130.2 mg/g and the breakthrough time of 86 and 124 minutes respectively. The adsorbent’s unique ability to high NOx adsorption affinity is a major breakthrough in this research.Several characterization techniques were used to identify the physical and chemical properties of HM, DP, IM-Co3O4/ACM catalyzed adsorbents,specifically the textural properties (BET), thermal decomposition (TGA), functional groups (FTIR), chemical composition (XRD) and the surface morphology (FESEM/ EDX) and active site analysis (TPD-NH4). The optimization of the independent variables that influences the adsorption capacity on HM-Co3O4/ACM catalyzed adsorbent by response surface methodology (RSM) was carried out. Using the optimized values of 1 mg as the amount of adsorbent, 400 mL/min for flow rate and 100 oC for column temperature, the experimental result for the adsorption capacity of SO2 and NOxwere 134.5 and 152.1 mg/g respectively. The statistical analysis revealed that the interaction between the independent variables and the adsorption capacity of SO2/NOx were very significant which confirmed the quality and suitability of models developed for the prediction of the process behavior. Furthermore, the deactivated HM-Co3O4/ACM catalyzed adsorbent was regenerated by deionized water and H2SO4 washing and subsequent thermal regeneration. The stability of the regenerated adsorbent was very good after five regeneration cycles with average regeneration efficiencies of 92.7% and 94.2% for SO2 and NOx. The key regeneration parameters including regenerating temperature, regenerating time and nitrogen stream flow rate were optimized using the response surface methodology (RSM) technique. The RSM results showed that the prediction and experimental results were in agreement where only 1.5% and 0.4% deviate in regeneration efficiencies (RE-SO2 and RE-NOx). The physicochemical, structural, textural, thermal and morphological properties of the regenerated adsorbent were also investigated. In conclusion, the adsorbent's unique ability to high NOx adsorption affinity was demonstrated. It was found that this feat depends on the adsorbates concentration in the flue gas, adsorbent preparation, synthesis method, operating temperature, the amount of oxygen and the relative humidity. The stability and performance revealed the potential of the adsorbent for effective approaches toward industrial application.